Why apprentices quit : a German case study - Hauschildt, Ursel [Verfasser]; Piening, Dorothea [Verfasser] (My University, 2013)
"In Germany, still more than 20% of all training contracts between apprentices and companies offering in-company training terminate at an early stage or later during the case of apprenticeship. These consistently high cancellation rates very often go with serious financial damage for companies involved and also affect the economy as a whole. Some training places remain vacant for the rest of a training year, other are never offered again. On the other hand young learners/apprentices loose precious time while pursuing a "wrong" career. Frustration and demoralisation of apprentices are the consequence. In 2011, IBB was asked to carry out a regional study on reasons of early termination of training contracts in the region of Leipzig and northern Saxony. This paper gives insights to the major backgrounds for such contract terminations and derives some recommendations for measures to prevent such drop-outs in future and that help to create more successful school-to-apprenticeship transitions." (Autorenreferat, BIBB-Doku)
Keywords: G 1.3.2.2.2 Verlauf (Erfolg / Abbruch); I 2.1.1.3 Sachsen; Ausbildungsabbruch; Ursache; Abbrecherquote; Region; Leipzig; Sachsen